Therapies in Refractory Metastatic Renal Cell Carcinoma - Stephanie Berg; Martin Angel; Kathryn E. Beckermann; Frede Donskov; Chung-Han Lee; Pavlos Msaouel; Rana R. McKay; Tian Zhang (Société Internationale d’Urologie Journal)
As the therapeutic landscape for metastatic clear cell renal cell carcinoma (mccRCC) expands to include vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR TKIs) and immunotherapies, new challenges are in place for evaluating and treating refractory disease. Assessing and managing refractory disease has several elements: (1) the mechanism(s) of front-line treatment, (2) timing of progressive disease, (3) rapidity and sites of progressing disease, (4) use of adjuvant therapy, and (5) incorporation of surgical and radiation techniques. These variables all have distinct impact on the biology of refractory or resistant mccRCC. A better understanding of the essential mechanisms of both primary and secondary immunotherapy resistance will inform biomarker development and therapeutic strategies in the refractory setting. This paper addresses the current understanding of treatment sequencing in refractory mccRCC, focusing on treatment options with prospective clinical trial data, considers refractory mccRCC after adjuvant immunotherapy, and incorporates radiation or surgical resection for oligoprogressive disease.